Development and Application of High Speed Gear Transmission Device without Pre-lubrication Startup - Zhang Xudong; Yu Zhangjiong (Jixie chuandong)
Aiming at the problem of the gearbox bearing and gear shaft locking due to the startup sequence error in the high- speed gear units startup process. Through the technical analysis of the gearbox casing structure,the bearing structure and the lubricating oil stations,of a high- speed gear transmission device without pre- lubricated startup is designed and developed. And the safety and reliability of the device are proved by experiment and field application.